Plan to Improve the Effectiveness of Short videos for Vietnam - Korea University of Information and Communication Technology - Nguyen, Thi Bich Tram (Vietnam-Korea University of Information and Communication Technology, 2025)
Graduation thesis of Business Administration; 2021-2025